STUDI TINGKAT PENGETAHUAN TENTANG METODE PENURUNAN BERAT BADAN PADA MAHASISWA OVERWEIGHT DI STIKES RS. BAPTIS KEDIRI - Prasetyorini, Hesti Titis; Febrijanto, Yoyok (Jurnal Penelitian STIKES Kediri, 2010)
Background    : The increasing of Overweight problem is proved that a lot of advertisement about decreasing weight product. People with Overweight that know how to control the body weight is important, they use various method to decrease weight of body until becoming normal weight, and keep maintaining that condition. The objective of this research is to identify the knowledge level about decreasing weight method to student with Overweight in Kediri Baptist Hospital Health Science College Method : This research was descriptive , Population was all students with Overweight in Kediri Baptist Hospital Health Science College. The samples were 30 respondents that meet inclusion criterion using total sampling. The variable was single variable namely knowledge about decreasing weight method to student with Overweight in Kediri Baptist Hospital Health Science College. The result of research from 30 respondents showed that student who had good level knowledge was 2 respondents (7%), enough level knowledge was 22 respondents (73%), and less level knowledge was 6 respondents (20%).    Conclusion : Conclusion of this research indicated that knowledge level about decreasing weight body method to student with Overweight in Kediri Baptist Hospital Health Science College